24 Anaemia in heart failure unit St. Michaels hospital dun laoghaire. (7th October 2015) - Mahon, C; Kenny, C; Lim, R; Earls, S; Travers, B; McDonald, K
Abstract : Background: Iron deficiency anaemia is a frequent finding in adults with heart failure (HF). The prevalence varying depending upon the population studied. 1, 2 The recent FAIR-HF trial, demonstrates the importance of iron metabolism in patients with HF. 3 Moreover, that a work-up evaluation for absolute or functional iron deficiency should be considered, and implementation of IV iron replacement for symptomatic improvement. In this audit we wish to evaluate the prevalence of anaemia and iron deficiency in our unit Method: This was a prospective single centre audit between 21 October and 18 November 2014. The cycle was repeated between 26 March and 26 April 2015. The audit standard was the WHO definition of anaemia. Results: Part 1: Demographics During cycle 1 Population: 86 patients were worked up for anaemia and iron deficiency. The average follow up time in Heart Failure Unit was 19.6 months There were more males than females in our population. Only one female patient is still menstruating. 74% of our population are HfREF (n = 64) versus 26% HfPEF (n = 22). During cycle 2 Population: 56 patients were worked up for anaemia and iron deficiency. The average follow up time in Heart Failure Unit was 20.4 months. There were more males than females in our population. 57% of our population are HfREF (n = 31) versus 43% HfPEF (n = 23). Part 2: Prevalence and incidence The prevalence of anaemia in our cohort was 48% during cycle 1 and 64.8% during cycle 2. Previous studies have found that the incidence of anaemia appears to increase with worsening functional class (from 9% for NYHA class I to 79% for class IV in one report). 4, 5 We found no association between the incidence of anaemia for NYHA, BNP or EF in our cohort. Part 3: Haematinic Screen Haematinic screens were not routinely ordered on all anaemic patients during cycle 1. No haematinic screen was found for 15 anaemic patients, an incomplete screen was carried out on 9 anaemic patients and a complete anaemic screen on 17 patient. A complete haematinic screen was carried out on 8 patients with normal Hb levels. Iron deficency was detected in 17 patients. Five patient with iron deficency were noted to have a normal Hb level. During cycle 2 and implementation of a routine strategy of a haematinic screening at initial programme visit or at annual review, if no such screen were on record, all patients had a haematinic screen. Summary: Iron deficiency management is not incorporated in the current ESC HF guidelines. 6 However, recent studies have raised interest in the importance in symptomatic and QUAL in of HfREF patients, and experts anticipate it's inclusion in future guidelines. Further given that there are few treatment strategies for HfPEF patients, management of iron deficiency in this cohort would be an area of interest to access any symptomatic and other clinical benefit. In this audit we successfully implemented a strategy of routine screening for iron deficiency, to capture all patients in both HfREF and HfPEF patients. Importantly, at present our cohort our stable from a heart failure perspective. In future direction and management of these patients we aim to implement a strategy of IV iron replacement based on recent FAIR-HF and CONFIRM-HF studies. 3, 7 References: De Silva R, Rigby AS, Witte KK, et al . Anemia, renal dysfunction, and their interaction in patients with chronic heart failure. Am J Cardiol. 2006;98 :391–398 Westenbrink BD, Visser FW, Voors AA, et al . Anaemia in chronic heart failure is not only related to impaired renal perfusion and blunted erythropoietin production, but to fluid retention as well. Eur Heart J. 2007;28 :166–171 Anker SD, Comin Colet J, Filippatos G, et al . Rationale and design of Ferinject assessment in patients with iron deficiency and chronic Heart Failure (FAIR-HF) study: a randomized, placebo-controlled study of intravenous iron supplementation in patients with and without anaemia. Eur J Heart Fail . 2009;11 :1084–1091 Silverberg DS, Wexler D, Sheps D, et al . The effect of correction of mild anemia in severe, resistant congestive heart failure using subcutaneous erythropoietin and intravenous iron: a randomized controlled study. J Am Coll Cardiol . 2001;37 :1775–1780 Van der Meer P, Groenveld HF, Januzzi JL Jr, et al . Erythropoietin treatment in patients with chronic heart failure: a meta-analysis. Heart 2009;95 :1309–1314 McMurray J, Adamopoulos S, Anker S, et al . ESC Guidelines for the diagnosis and treatment of acute and chronic heart failure 2012. Eur Heart J . 2012;33 :1787–1847 Ponikowski P, van Veldhuisen DJ, Comin-Colet J, et al . Beneficial effects of long-term intravenous iron therapy with ferric carboxymaltose in patients with symptomatic heart failure and iron deficiency. Eur Heart J . 2015;36 (11):657–68